Migrant mothering and mobile phones : negotiations of transnational identity - Chib, Arul (2020)
Transnational mothers working in foreign countries face the challenges of providing “intensive” mothering to their children from a distance, and risk being subject to the “deviancy” discourse of mothering. This paper investigates the role of mobile phone usage, via voice, text messages, and social networking sites, in dealing with the tensions and ambivalence arising from transnational mothering as a dialectical process. We surveyed 42 Filipina and Indonesian foreign domestic workers (FDWs) in Singapore using a mixture of quantitative and qualitative methods. FDWs addressed tensions arising out of societal expectations of motherhood and their own anxieties about children’s well-being. The reluctant obsessive struggled to maintain a balance between an intensive nurturing style and a deviant mode of mothering that respected the growing independence of the children. The diverted professional had to balance the financial empowerment of being the primary breadwinner with the risk of surrogate motherhood for the employer’s children subsuming the care provided to her own. The remote-control parent shared mothering responsibilities with caregivers, usually relatives, who acted as a contradictory proxy presence for intensive mothering. The incomplete union of stressed marital parenting put further pressure on the romantic and sexual identities of migrant women. Transnational mothers utilized mobile phones actively as a tool to negotiate and redefine identities and relationships that created fissures in their sense of self. These included the management of third-party relationships, withholding of emotions or information, and engaging in counterintuitive phenomenon such as restricting, or actively dis-engaging from, mobile phone usage as a communication strategy. The paper calls for future research into the multiple, and interacting, social identities assumed and managed by transnational mothers, and the complex role played by mobile phones in the constant process of negotiation by agentic, self-relective and multifaceted women.